Emissions from agricultural sector and financial development in Nigeria: an empirical study - Maji, Ibrahim Kabiru; Habibullah, Muzafar Shah; Saari, Mohd Yusof (Faculty of Economics and Management, Universiti Putra Malaysia, 2016)
The present paper investigates the impact of financial development on carbon dioxide (CO2) emissions from the agricultural sector in Nigeria. In an agricultural dependent economy such as Nigeria, the nation depends on the agriculture sector to feed its growing population and to foster economic development. However, in this study, we consider CO2 emission from the agriculture sector to be the indicator for the environmental quality. We posit that like any other developing economy, there is a role play by the financial sector to promote growth and progress in enhancing economic development. The pursuit for economic development will ultimately result in environmental pollution. We employ the Autoregressive Distributed Lag (ARDL) approach on annual data spanning from 1971-2011. The control variables included in this study comprises national income, energy consumption, foreign direct investment and population. Our results suggest that all variables exhibit long-run relationship with CO2 emissions from the agricultural sector. Financial development and national income show negative relationship with CO2 emissions from agricultural sector, suggesting that economic development has not taken place at the expense of CO2 emissions. However, the increase in population and foreign direct investment has led to an increase in CO2 emissions from the agricultural sector.